Aplicación del mucilago de cacao (Theobroma cacao) como medida de control del musgo (Rigodium implexum) y su efecto en la producción del Cacao Nacional - Reasco Tigua , Emily Dayana (2023)
The presence of moss (Rigodium implexum) in cocoa plants (Theobroma cacao) has a negative impact on production. The objective of the research was: To evaluate the application of cocoa mucilage as a control measure of the moss R. implexum and its effect on the production of the National Cocoa. The study was carried out in Buena Fe Canton, using a Completely Randomized Block Design (CRBD) with four treatments, four replications and five experimental units. The treatments used were: chemical control using copper oxychloride and mucilage at concentrations of 75%, 50% and 25%, respectively. The results obtained showed that both the chemical control and the use of mucilage at 50% and 25% produced good averages in terms of the number of flowers and fruits. However, the application of 25% mucilage showed greater control over the moss over a five-week period. Data collected weekly revealed a moss decline of 0% in the first week, 40% in the second week, 50% in the third week, 63.75% in the fourth week and 77% in the fifth week. It can be stated that the use of organic substances, such as cocoa mucilage, offers several effective alternatives for the control of R. implexum moss on cocoa plants. These findings are relevant for farmers seeking to improve cocoa production by minimizing the negative effects of this moss species. Keywords: Mucilage, cocoa, moss, production